Ma’had Al-Zaytun Shifts Towards Online Learning: Are They Satisfied? - Norazzila Shafie,; Nurfadhlin Mohd Jaafar,; Habsah Musliman,; Nur Darmiyantie Mohamed,; Mohd Zabri Mohd Zun,; Fazilah Razali,; Hamidah Mat, (ASEAN Journal of Open and Distance Learning, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has caused disruptions in the delivery of instruction at all levels of educational institutions, whether those institutions are elementary, secondary, or postsecondary in nature. Due to this pandemic, a group of secondary school international students from Malaysia were unable to conduct face-to-face classes in Ma’had Al-Zaytun International School in Indonesia and were forced to shifts towards fully online learning mode. This study aims to explore students’ satisfaction and motivation in the online learning interaction at this international school. Based on the transaction distance theory, this study focuses on four modes of interaction, namely (i) interaction between students and teachers, (ii) interaction between students, (iii) interaction between students and learning materials, and (iv) interaction between students and interfaces. A qualitative study was employed to investigate the satisfaction and motivation of students using a semi-structured interview, class observation, and daily class report. Findings indicate that the majority of the students were satisfied with these online learning interactions and teachers were the main factors that motivated them to learn. According to this study as well, parents are also a factor that affects student participation in online learning. Students who receive encouragement and support from their parents are more likely to be satisfied with this online learning, which suggest that future research could be done to further examine. (Abstract by authors)